Pengembangan Situs Web Terintegrasi Bagi Berbagai Amal Usaha Di Muhammadiyah Cabang Kartasura - Septiawan, Albert; , Husni Thamrin S.T., M.T., Ph.D (2017)
Integrated Websiter for Amal Usaha Muhammadiyah (AUM) on Muhammadiyah Cabang Kartasura is a facility that include all web sites for AUM (sub site) in Kartasura region such as schools and hospitals that help Muhammadiyah Cabang Kartasura to record recent data which are updated timely. It helps AUM internal staff to share information quickly, accurately and timely to the surrounding community. Other benefit using a web portal is the community can easily and directly access latest information about related AUM independently like daily doctor schedule in the hospital before they go for treatment. Also when they want to know information about school profile, achievement, location, events and student admissions. In addition, parent website (Muhammadiyah Cabang Kartasura) can directly publish important information and announcement to the surrrounding community because one of this web portal feature enable that important information visible on all sub website without direct access to Muhammadiyah Cabang Kartasura web page. This web portal is designed with waterfall method and developed using Laravel PHP Framework with mysql as its database management system. Data collection technique used by the researcher are observation and interviews. The result of this study is a integrated website contain Muhammadiyah Cabang Kartasura website as the parent website and subwebsite belongs to each of AUM that can be manage independently also there are contributors that can submit news draft to share in one of website